Analisis Peforma Dan Komsumsi Bahan Bakar Pada Honda Tiger 2006 Menggunakan Piston Standar Dan Piston Pro Neotech - Muchlisinalahuddin Muchlisnalahuddin; Riza Muharni; Usriadi Usriadi (Politeknik Negeri Padang, 2022)
the engine performance is very important at the automotive world, especially on 4-stroke motorcycles, where most people want the engine performance to be better and more economically. In this case to improve engine performance is done by changing the piston on the motor. With a different piston shape can increase the compression ratio. The purpose of this study is to determine changes in compression ratio, torque, power and fuel consumption, after replacing the piston. The test was carried out on a 2006 Honda Tiger, with a standard piston specification with a diameter of 64.5 mm (flat surface) and replaced with a 64.5 mm pro newtech piston (convex surface) by using Pertamax 92 fuel. The results obtained from the comparison of the compression value of 1, 6 : 1, 12.65 ft-lbs of torque, and 2.87 ft-lbs of power so that fuel consumption increases by 5.685%